IN VITRO ANTIMICROBIAL ACTIVITY, HIGH-PERFORMANCE THIN-LAYER CHROMATOGRAPHY, AND GAS CHROMATOGRAPHY-MASS SPECTROMETRY ANALYSIS OF ETHANOLIC SEED EXTRACT OF FICUS BENGHALENSIS LINN - G, Vimala; Shoba F, Gricilda (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: In the traditional medicine, Ficus benghalensis is used for the treatment of ulcer, diabetes, inflammation, liver disorders, urinary disorders, vomiting, vaginal complains, and fever and as a bitter tonic. However, despite its traditional usage as an antimicrobial agent, there is no information regarding its effectiveness in infections caused by pathogenic microbes. Hence, we evaluated the ethanolic extract of the seeds of F. benghalensis for its antimicrobial activity. Methods: The antimicrobial activity of the extract at five different concentrations was tested against few common human pathogenic microorganisms by agar disc diffusion assay. Streptomycin (10 Î¼g/ml) and Amphotericin B (10 Î¼g/ml) were used as standards for antibacterial and antifungal studies, respectively. Few phenolic compounds were identified by standard high-performance thin-layer chromatography (HPTLC) and gas chromatography-mass spectrometry (GC-MS) techniques. Results: The zone of inhibition was extremely great for Pseudomonas aeruginosa (19 mm), Enterococcus faecalis (18 mm), and Aspergillus niger (13 mm). Moreover, through HPTLC analysis, few phenolic compounds such as quercetin (Rf value - 0.54), gallic acid (Rf value - 0.45), and tannic acid (Rf value - 0.45) were identified. A total of seven compounds were identified in the extract using GC-MS analysis. Conclusions: The results, therefore, clearly indicate that the crude extract from F. benghalensis seeds could be used as a potential source of natural antimicrobial agent due to the presence of the phytoconstituent quercetin, gallic acid, and tannic acid in abundance along with other active compounds and support the traditional use of the plant in the treatment of infections.